(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The comment analyses a recent judgement of the Supreme Court of Italy grounded on a claim for damages against a gynaecologist who, while making a prenatal diagnostic, omitted to detect the presence of malformations in a foetus. The claim of the plaintiff refers to the violation of the right “to born in a family not fully prepared to welcome a disabled child”. The Supreme Court differently qualified the claim of the plaintiffs as a “linguistic mimetism” of a different right, precisely the “right not to be born” (wrongful life) and did not award the child any compensation. In commenting the case, the author integrates the juridical analysis by the linguistic one, in order to verify whether the juridical requalification of the plaintiffs’ claim by the Court, as grounded on the linguistic re-formulation of that claim, leads to a violation of the necessary relation between the request of the plaintiffs and the decision of the judge, provided by art. 112 of the Italian Code of civil procedure.